TRIP-1 Promotes the Assembly of an ECM That Contains Extracellular Vesicles and Factors That Modulate Angiogenesis - Chen, Yinghua; George, Anne (Frontiers in Physiology, 2018)
Transforming growth factor beta receptor II interacting protein 1 (TRIP-1) was recently localized in the mineralized matrices of bone and dentin. The function of TRIP-1 in the ECM is enigmatic, as it is known to function as an intracellular endoplasmic reticulum (ER) protein during protein synthesis. Based on its localization pattern in bones and teeth, we posited that TRIP-1 must function as a regulatory protein with multiple functions during mineralization. In this study, we determined the in vivo function of TRIP-1 by an implantation assay performed using recombinant TRIP-1 and TRIP-1 overexpressing and knocked down cells embedded in a 3D biomimetic scaffold. After 4 weeks, the subcutaneous tissues from TRIP-1 overexpressing cells and scaffolds containing recombinant TRIP-1 showed higher expression levels of several ECM proteins such as fibronectin and collagen I. Picrosirius red and polarized microscopy was used to identify the birefringence of the collagen fibrils in the extracellular matrix (ECM). Interestingly, knockdown of TRIP-1 resulted in lower fibronectin and downregulation of the activation of the ERK MAP kinase. We further demonstrate that TRIP-1 overexpression leads to higher expression of pro-angiogenic marker VEGF and downregulation of anti-angiogenic factors such as PEDF and thrombospondin. Field emission scanning electron microscope (FESEM) results demonstrated that TRIP-1 overexpressing cells released large amount of extracellular microvesicles which were localized on the fibrillar matrix in the ECM. Overall, this study demonstrates that TRIP-1 can promote secretion of extracellular vesicles, synthesis of key osteogenic ECM matrix proteins and promote angiogenesis.